Genesis of pseudo-sand structure in Oxisols from Brazil – A review - Martinez, Pedro; Souza, Ivan F. (Geoderma Regional, 2020)
Pseudo-sands are soil microaggregates with less than 1 mm diameter that are not dispersible in water even after 16 h of shaking treatment. The physical stability of pseudo-sands against dispersion may affect the extent to which organic matter is retained in the soil, particularly in Oxisols where pseudo-sands occur throughout the A and B horizons. It is not completely understood the pedological chain of events behind the development of such strong physical stability of pseudo-sand and its effects on the turnover of organic matter found inside the microaggregates. To address this issue, we review the theories about the genesis of pseudo-sands in Oxisols. This review was conducted to support future studies on microaggregate formation and mineral-organic associations in Oxisols. The genesis of pseudo-sands in Oxisols is attributed to the following processes: (i) residual accumulation of pedogenic Fe- and/or Al-(hydr)oxides that weld kaolinite particles; (ii) linkages between Fe- and/or Al-(hydr)oxides, kaolinite, and organic matter, which increase cohesive forces among clay particles and create pore-space area; (iii) mechanical fracturing of mineral materials by long-term wetting-drying and erosion-deposition cycles; and (iv) long-term bioturbation that reduces size and increases physical stability of aggregates that are modified by soil mesofauna (e.g., ant and termite) to construct chambers and mounds. The magnitude of each of these four processes should vary as a function of soil depth, parent material, erosion-deposition dynamic, and vegetation-driven bioturbation intensity. The retention of organic carbon in Oxisols is more efficient when mineral-organic associations are backed up by the physical protection provided by occlusion of organic matter inside the pseudo-sands. Future investigations should determine to what extent the internal structure (e.g., intra-aggregate pore tortuosity) of pseudo-sand causes the separation of organic matter from microbes/decomposers and creates a physical barrier that decreases oxygen availability or oxygen/water ratios to decomposers. •The genesis of pseudo-sands in Oxisols is constrained by geochemical, physical-mechanical, and biological factors.•Geochemical interactions between kaolinite-oxides-organic-matter enhance cohesion force between clay particles.•Mechanical fragmentation of soil materials is boosted by long-term wetting-drying and erosion-deposition cycles.•Long-term bioturbation by ants, termites, and roots reduces aggregate size and increases physical stability.•C-cycling within pseudo-sand is more affected by occlusion of organic matter than by sorption on mineral surfaces.